Zirconium-doped all-inorganic perovskite quantum dot glass as well as preparation method and application thereof
By doping zirconium in perovskite quantum dot glass, the problems of instability and complex preparation process of existing perovskite quantum dot glass are solved, and high quantum efficiency and humidity and heat aging stability are improved, with potential wide color gamut display applications.
Patent Information
- Application Number
- CN202311233216.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The existing perovskite quantum dot glass has instability in long-term use, and the preparation process is complex and time-consuming, with low quantum efficiency and insufficient humidity and heat aging stability.
Doping a small amount of zirconium in all-inorganic perovskite quantum dot glass, adjusting the viscosity and thermal expansion coefficient of the glass, promote the crystallization of quantum dots in the glass matrix, shorten the crystallization time, and improve the quantum efficiency and humidity-heat aging stability of the glass.
It significantly improves the quantum efficiency, humidity and heat aging stability and blue light stability of all-inorganic perovskite quantum dot glass, simplifies the preparation process, reduces costs, and has potential application value in the field of wide color gamut display.
Smart Images

Figure CN119683861A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum dot luminescent materials, and specifically relates to a zirconium-doped all-inorganic perovskite quantum dot glass and a preparation method and application thereof. Background Art
[0002] Semiconductor perovskite quantum dots, especially all-inorganic CsPbX3 (X=Cl, Br or I) perovskite quantum dots (PQDs), are considered to be a new generation of optoelectronic materials. Due to its excellent optical properties such as high photoluminescence quantum yield, narrow-band emission, adjustable band gap and wide color gamut, it has become a research hotspot. It has potential applications in light-emitting diodes (LEDs), displays, lasers, photodetectors, solar energy and other fields. However, colloidal PQDs are easily decomposed and ineffective when exposed to air, water, high temperature and radiation. This instability limits their long-term use in practice. Therefore, the stability of PQDs is improved by surface modification, ligand exchange, polymer or silica encapsulation. However, these methods involve complex chemical treatments, non-dense structures and incomplete surface protective layer coatings, which have no significant effect on the long-term stability of PQDs. Therefore, PQDs are crystallized in a dense inorganic oxide glass network to prepare PQDs glass with good mechanical, thermal and chemical stability.
[0003] At present, Zn / Cd / Pb-based sulfide quantum dot-doped glass has long been successfully developed as a type of transparent material. In 2016, Wang et al. successfully precipitated CsPbBr3 quantum dots in phosphate glass for the first time through traditional melt quenching and subsequent heat treatment, which also opened a new chapter in all-inorganic CsPbX3 perovskite quantum dot glass. So far, through traditional melt quenching and subsequent heat treatment methods, the in-situ growth of all-halide perovskite quantum dots in glass has been achieved, and its optical properties have also been widely studied. In addition, using the stability of quantum dot glass, the application of quantum dot glass (QDs@glass) in solid-state lighting, backlight display, anti-counterfeiting and other fields has also been explored.
[0004] However, compared with the quantum efficiency of colloidal PQDs, PQDs quantum dot glass is relatively low, and the preparation process of PQDs quantum dot glass is relatively complicated, including calcination, annealing, and heat treatment processes, especially the heat treatment temperature time is too long, up to more than ten hours. In addition, PQDs quantum dot glass has higher requirements for wet heat aging stability.
[0005] Therefore, providing a perovskite quantum dot glass with high quantum efficiency and high moisture-heat aging stability is a hot topic that needs to be studied urgently. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a zirconium-doped all-inorganic perovskite quantum dot glass and its preparation method and application. The present invention, by doping a small amount of zirconium in the all-inorganic perovskite quantum dot glass, not only significantly increases the viscosity of the glass, reduces the thermal expansion coefficient, makes it easier for quantum dots to crystallize in the glass matrix, shortens the crystallization process, but also significantly improves the quantum efficiency of the all-inorganic perovskite quantum dot glass, as well as the wet heat aging stability and blue light stability, which has potential application value in the field of wide color gamut display.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a zirconium-doped all-inorganic perovskite quantum dot glass. In terms of mole percentage, the zirconium-doped all-inorganic perovskite quantum dot glass comprises:
[0009] Glass matrix: 68-89%, zirconium-containing compound: 0.1-1%, all-inorganic perovskite quantum dot matrix: 11-28%.
[0010] The present invention dopes a small amount of zirconium into the all-inorganic perovskite quantum dot glass, which not only significantly increases the viscosity of the glass and reduces the thermal expansion coefficient, making it easier for the quantum dots to crystallize in the glass matrix and shortening the crystallization process, but also significantly improves the quantum efficiency of the all-inorganic perovskite quantum dot glass, as well as the wet-heat aging stability and blue light stability. It has potential application value in the field of wide color gamut display.
[0011] In the present invention, doping a small amount of zirconium into the all-inorganic perovskite quantum dot glass can help the glass to stably exist in an alkaline environment formed by water vapor during the wet heat aging process, thereby greatly improving the wet heat aging stability of the glass.
[0012] In the present invention, the molar percentage of the glass matrix is 68-89%, for example, it can be 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86% or 88%.
[0013] In the present invention, the molar percentage of the all-inorganic perovskite quantum dot matrix is 11-28%, for example, it can be 11%, 13%, 15%, 17%, 19%, 21%, 23%, 25% or 27%, etc.
[0014] In the present invention, the molar percentage of the zirconium-containing compound is 0.1-1%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0015] In the present invention, if the molar percentage of the zirconium-containing compound is too low, that is, too little zirconium is doped, there is no obvious improvement effect on the quantum efficiency and the wet-heat stability; if the molar percentage of the zirconium-containing compound is too high, that is, too much zirconium is doped, there is no obvious improvement effect on the quantum efficiency and the wet-heat stability.
[0016] As a preferred technical solution of the present invention, the raw material composition of the glass matrix comprises, in terms of molar percentage:
[0017] SiO2: 25-35%, B2O3: 35-40%, ZnO: 5-8%, CaO: 3-6%.
[0018] In the present invention, the molar percentage of SiO2 is 25-35%, for example, it can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, etc.
[0019] In the present invention, the molar percentage of B2O3 is 35-40%, for example, it can be 35%, 36%, 37%, 38%, 39% or 40%.
[0020] In the present invention, the molar percentage of ZnO is 5-8%, for example, it can be 5%, 6%, 7% or 8%.
[0021] In the present invention, the molar percentage of CaO is 3-6%, for example, it can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.
[0022] Preferably, the glass matrix is a borosilicate glass matrix.
[0023] As a preferred technical solution of the present invention, the raw material composition of the all-inorganic perovskite quantum dot matrix comprises, in terms of molar percentage:
[0024] Cs2CO3: 2-5%, PbO: 2-5%, KX: 7-18%, X=at least one of Cl, Br and I.
[0025] In the present invention, the molar percentage of Cs2CO3 is 2-5%, for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0026] In the present invention, the molar percentage of PbO is 2-5%, for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0027] In the present invention, the molar percentage of KX is 7-18%, for example, it can be 7%, 9%, 11%, 13%, 15%, 16% or 18%.
[0028] Preferably, the all-inorganic perovskite quantum dot matrix comprises CsPbBrI2.
[0029] Preferably, in terms of mole percentage, the composition of KX comprises:
[0030] KBr: 2-8%, KI: 5-10%.
[0031] In the present invention, the molar percentage of KBr is 2-8%, for example, it can be 2%, 3%, 8%, 5%, 6%, 7% or 8%.
[0032] In the present invention, the molar percentage of KI is 5-10%, for example, it can be 5%, 6%, 7%, 8%, 9% or 10%.
[0033] As a preferred technical solution of the present invention, the zirconium-containing compound includes at least one of zirconium dioxide, zirconium silicate and calcium zirconate, preferably zirconium dioxide.
[0034] In the present invention, ZrO2 belongs to the network extracellular oxide (network extracellular oxide cannot form glass alone, does not participate in the network, and is generally outside the network). 4+ The electric field strength is high, the single bond energy is large, and the coordination number is greater than 6. Because the Zr-O bond is highly ionic, the oxygen ion O 2- It is easy to get rid of the bondage of cations and is a provider of "free oxygen", which plays a role in breaking the network, but its cations (especially highly charged cations) are also accumulators of broken bonds. This characteristic has a certain promoting effect on the crystallization of glass, thereby reducing the crystallization time and improving the quantum efficiency. In addition, ZrO2 has a low solubility in silicate glass, the Zr-O bond has a strong ionicity and a large single bond energy, and Zr 4+ The larger ion radius can improve the compactness of the glass network structure and increase the glass density, thereby improving water / moisture and heat resistance stability.
[0035] Preferably, in terms of molar percentage, the content of the zirconium-containing compound is 0.3-0.7%, for example, 0.3%, 0.4%, 0.5%, 0.6% or 0.7%.
[0036] In a second aspect, the present invention provides a method for preparing the zirconium-doped all-inorganic perovskite quantum dot glass as described in the first aspect, the preparation method comprising the following steps:
[0037] (1) mixing the raw materials of the matrix glass, and then melting the obtained mixture to obtain a molten product;
[0038] (2) heat treating the molten product to obtain the zirconium-doped all-inorganic perovskite quantum dot glass.
[0039] The preparation method provided by the present invention has simple process, readily available raw materials, strong repeatability, and is easy to prepare on a large scale. In addition, the preparation method can greatly shorten the time of heat treatment crystallization and reduce costs.
[0040] As a preferred technical solution of the present invention, the mixing process in step (1) is accompanied by grinding.
[0041] Preferably, the melting treatment in step (1) is carried out in an air atmosphere.
[0042] Preferably, the temperature of the melt treatment in step (1) is 1000-1200°C, for example, it can be 1000°C, 1050°C, 1100°C, 1150°C or 1200°C.
[0043] Preferably, the holding time of the melting treatment in step (1) is 5-20 min, for example, 5 min, 10 min, 15 min or 20 min.
[0044] As a preferred technical solution of the present invention, before the molten product is heat-treated in step (2), the molten product is first transferred to a mold at room temperature.
[0045] It should be noted that normal temperature refers to 25±5°C, for example, it can be 20°C, 25°C or 30°C.
[0046] It should be noted that the heat treatment process is also the crystallization process. Before the heat treatment, the quantum dots in the glass matrix have not been formed and exist in the form of single ions. During the heat treatment process, the heat energy provided can promote the ions to form compounds and further form quantum dots. The crystallization mechanism is: Cs + +Br - =CsBr;Pb 2+ +Br - =PbBr2;Pb 2+ +I - =PbI2; CsBr+PbBr2+PbI2=CsPbIBr2.
[0047] As a preferred technical solution of the present invention, the temperature of the heat treatment is 500-550°C, for example, it can be 500°C, 510°C, 520°C, 530°C, 540°C or 550°C.
[0048] In the present invention, if the heat treatment temperature is too low, the quantum dots cannot be crystallized / crystallized incompletely in the glass matrix; if the heat treatment temperature is too high, the quantum dots grow too large, causing the quantum dot glass to become devitrified (lose transparency), reducing light transmittance and lowering quantum efficiency.
[0049] Preferably, the heat treatment time is 3-12 h, for example, it can be 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc., preferably 7-10 h.
[0050] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0051] (1) SiO2, B2O3, ZnO, CaO, Cs2CO3, PbO, KX and zirconium dioxide are fully ground and mixed according to their respective mole percentages to obtain a mixed powder;
[0052] (2) In an air atmosphere, the mixed powder is melt-treated at 1000-1200° C. for 5-20 min. After the melting treatment, the molten product is transferred to a mold at room temperature and then heat-treated at 500-550° C. for 3-12 h to achieve shaping and obtain the zirconium-doped all-inorganic perovskite quantum dot glass.
[0053] In a third aspect, the present invention provides a use of the zirconium-doped all-inorganic perovskite quantum dot glass as described in the first aspect in the preparation of a luminescent material.
[0054] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The present invention dopes a small amount of zirconium into the all-inorganic perovskite quantum dot glass, which not only significantly increases the viscosity of the glass and reduces the thermal expansion coefficient, making it easier for quantum dots to crystallize in the glass matrix and shortening the crystallization process, but also significantly improves the quantum efficiency and stability of the all-inorganic perovskite quantum dot glass.
[0057] (2) The main emission peak of the glass prepared by the present invention is located at 633nm, the half-peak width is 32nm, and the quantum efficiency under the excitation of blue light with a wavelength of 420nm can reach 80%. It has good moisture and heat stability and blue light stability, and has potential application value in the field of wide color gamut display.
[0058] (3) The preparation method provided by the present invention has a simple process, and the raw materials are readily available, and the preparation is highly repeatable and easy to scale up. In addition, the preparation method can greatly shorten the time of heat treatment crystallization and reduce the cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1This is a comparison chart of the emission spectra of the all-inorganic perovskite quantum dot glass provided in Example 1-2 and Comparative Example 1-2 of the present invention under excitation at a wavelength of 420 nm.
[0060] Figure 2 This is a stability curve diagram of the all-inorganic perovskite quantum dot glass provided in Examples 1-4 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Example 1
[0063] This embodiment provides a zirconium-doped all-inorganic perovskite quantum dot glass. In terms of mole percentage, the zirconium-doped all-inorganic perovskite quantum dot glass comprises:
[0064] Glass matrix: 76.5%, zirconium dioxide: 0.5%, all-inorganic perovskite quantum dot matrix: 23%;
[0065] The composition of the glass matrix includes: SiO2: 26.5%, B2O3: 40%, ZnO: 6%, CaO: 4%; the composition of the all-inorganic perovskite quantum dot matrix includes: Cs2CO3: 3%, PbO: 4%, KBr: 6%, KI: 10%.
[0066] This embodiment also provides a method for preparing the above-mentioned zirconium-doped all-inorganic perovskite quantum dot glass, the preparation method comprising the following steps:
[0067] (1) SiO2, B2O3, ZnO, CaO, Cs2CO3, PbO, KBr, KI and zirconium dioxide are weighed by mole percentage and fully ground and mixed in an agate mortar, wherein SiO2, B2O3, ZnO and CaO are borosilicate glass matrices, and Cs2CO3, PbO, KBr and KI are raw materials for synthesizing CsPbBrI2, to obtain a mixed powder;
[0068] (2) The mixed powder is loaded into a corundum crucible, and melt-treated at 1100° C. for 15 min in an air atmosphere. After the melting treatment, the obtained molten product is transferred to a mold at room temperature, and then heat-treated at 550° C. for 5 h. After natural cooling, the crystallized zirconium-doped all-inorganic perovskite quantum dot glass is obtained.
[0069] Example 2
[0070] The difference between this embodiment and embodiment 1 is that the heat treatment time in step (2) is 10 hours.
[0071] The remaining preparation methods and parameters are consistent with those in Example 1.
[0072] Example 3
[0073] This embodiment provides a zirconium-doped all-inorganic perovskite quantum dot glass. In terms of mole percentage, the zirconium-doped all-inorganic perovskite quantum dot glass comprises:
[0074] Glass matrix: 75.5%, zirconium dioxide: 1%, all-inorganic perovskite quantum dot matrix: 23.5%;
[0075] The composition of the glass matrix includes: SiO2: 32%, B2O3: 35%, ZnO: 5%, CaO: 3.5%; the composition of the all-inorganic perovskite quantum dot matrix includes: Cs2CO3: 5%, PbO: 4.5%, KBr: 8%, KI: 6%.
[0076] This embodiment also provides a method for preparing the above-mentioned zirconium-doped all-inorganic perovskite quantum dot glass, the preparation method comprising the following steps:
[0077] (1) SiO2, B2O3, ZnO, CaO, Cs2CO3, PbO, KBr, KI and zirconium dioxide are weighed by mole percentage and fully ground and mixed in an agate mortar, wherein SiO2, B2O3, ZnO and CaO are borosilicate glass matrices, and Cs2CO3, PbO, KBr and KI are raw materials for synthesizing CsPbBrI2, to obtain a mixed powder;
[0078] (2) The mixed powder is loaded into a corundum crucible, and melt-treated at 1150° C. for 8 min in an air atmosphere. After the melting treatment, the molten product is transferred to a mold at room temperature, and then heat-treated at 530° C. for 10 h. After natural cooling, the crystallized zirconium-doped all-inorganic perovskite quantum dot glass is obtained.
[0079] Example 4
[0080] This embodiment provides a zirconium-doped all-inorganic perovskite quantum dot glass. In terms of mole percentage, the zirconium-doped all-inorganic perovskite quantum dot glass comprises:
[0081] Glass matrix: 78.3%, zirconium dioxide: 0.7%, all-inorganic perovskite quantum dot matrix: 21%;
[0082] The composition of the glass matrix includes: SiO2: 30%, B2O3: 37%, ZnO: 7%, CaO: 4.3%; the composition of the all-inorganic perovskite quantum dot matrix includes: Cs2CO3: 3%, PbO: 5%, KBr: 5%, KI: 8%.
[0083] This embodiment also provides a method for preparing the above-mentioned zirconium-doped all-inorganic perovskite quantum dot glass, the preparation method comprising the following steps:
[0084] (1) SiO2, B2O3, ZnO, CaO, Cs2CO3, PbO, KBr, KI and zirconium dioxide are weighed by mole percentage and fully ground and mixed in an agate mortar, wherein SiO2, B2O3, ZnO and CaO are borosilicate glass matrices, and Cs2CO3, PbO, KBr and KI are raw materials for synthesizing CsPbBrI2, to obtain a mixed powder;
[0085] (2) The mixed powder is loaded into a corundum crucible, and melt-treated at 1120° C. for 12 min in an air atmosphere. After the melting treatment, the obtained molten product is transferred to a mold at room temperature, and then heat-treated at 550° C. for 8 h. After natural cooling, the crystallized zirconium-doped all-inorganic perovskite quantum dot glass is obtained.
[0086] Example 5
[0087] The difference between this embodiment and embodiment 1 is that the molar percentage of SiO2 in the glass matrix is adjusted to 26.9%, and the molar percentage of zirconium dioxide is adjusted to 0.1%.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 6
[0090] The difference between this embodiment and embodiment 1 is that the molar percentage of SiO2 in the glass matrix is adjusted to 26.7%, and the molar percentage of zirconium dioxide is adjusted to 0.3%.
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Example 7
[0093] The difference between this embodiment and embodiment 1 is that the temperature of the heat treatment in step (2) is 450°C.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Example 8
[0096] The difference between this embodiment and embodiment 1 is that the temperature of the heat treatment in step (2) is 600°C.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Comparative Example 1
[0099] The difference between this comparative example and Example 1 is that zirconium dioxide is not added in step (1), and the contents of the remaining components are:
[0100] SiO2: 27%, B2O3: 40%, ZnO: 6%, CaO: 4%, Cs2CO3: 3%, PbO: 4%, KBr: 6%, KI: 10%.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Comparative Example 2
[0103] The difference between this comparative example and Example 2 is that zirconium dioxide is not added in step (1), and the contents of the remaining components are:
[0104] SiO2: 27%, B2O3: 40%, ZnO: 6%, CaO: 4%, Cs2CO3: 3%, PbO: 4%, KBr: 6%, KI: 10%.
[0105] The rest of the preparation methods and parameters were the same as those in Example 2.
[0106] Figure 1 A comparison chart of the emission spectra of the all-inorganic perovskite quantum dot glasses prepared in Example 1-2 and Comparative Example 1-2 under excitation at a wavelength of 420 nm is shown. It can be seen from the figure that the luminescence intensity of the sample heat-treated for 5 hours in Example 1 is close to that of the sample heat-treated for 10 hours in Comparative Example 1, and the luminescence intensity of the sample heat-treated for 10 hours in Example 2 is significantly higher than that of the sample heat-treated for 10 hours in Comparative Example 1, which indicates that doping zirconium dioxide can significantly improve the fluorescence intensity and has a better crystallization tendency. At the same time, only a shorter heat treatment time is required to achieve the optical properties of the sample in Comparative Example 1. Similarly, extending the heat treatment crystallization time can significantly improve the luminescence intensity of the sample.
[0107] Comparative Example 3
[0108] The difference between this comparative example and Example 3 is that zirconium dioxide is not added in step (1), and the contents of the remaining components are:
[0109] SiO2: 33%, B2O3: 35%, ZnO: 5%, CaO: 3.5%, Cs2CO3: 5%, PbO: 4.5%, KBr: 8%, KI: 6%.
[0110] The rest of the preparation methods and parameters were the same as those in Example 3.
[0111] Comparative Example 4
[0112] The difference between this comparative example and Example 4 is that zirconium dioxide is not added in step (1), and the contents of the remaining components are:
[0113] SiO2: 30%, B2O3: 37%, ZnO: 7%, CaO: 5%, Cs2CO3: 3%, PbO: 5%, KBr: 5%, KI: 8%.
[0114] The rest of the preparation methods and parameters were the same as those in Example 4.
[0115] Figure 2 The stability curves of the all-inorganic perovskite quantum dot glass provided by Examples 1-4 and Comparative Examples 1-4 are shown. It can be seen from the figure that with the extension of time, the fluorescence intensity decay of the all-inorganic perovskite quantum dot glass provided by Comparative Examples 1-4 decreases rapidly, indicating that the doping of zirconium dioxide has a good effect on improving the wet-heat aging stability.
[0116] Comparative Example 5
[0117] The difference between this comparative example and Example 1 is that the molar percentage of SiO2 in the glass matrix is adjusted to 26.95%, and the molar percentage of zirconium dioxide is adjusted to 0.05%.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 6
[0120] The difference between this comparative example and Example 1 is that the molar percentage of SiO2 in the glass matrix is adjusted to 25.5% and the molar percentage of zirconium dioxide is adjusted to 1.5%.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Performance Testing
[0123] The quantum efficiency and wet-heat aging stability tests were performed on the all-inorganic perovskite quantum dot glasses prepared in the above examples and comparative examples.
[0124] Stability test: Aging for 170h in an air environment at 65℃ / 95%RH, and testing the ratio of fluorescence intensity to initial fluorescence intensity.
[0125] The test results are shown in Table 1.
[0126] Table 1
[0127]
[0128]
[0129] analyze:
[0130] It can be seen from the above table that the present invention, by doping a small amount of zirconium into the all-inorganic perovskite quantum dot glass, not only makes it easier for quantum dots to crystallize in the glass matrix, shortening the crystallization process, but also significantly improves the quantum efficiency and wet-heat aging stability of the all-inorganic perovskite quantum dot glass, and has potential application value in the field of wide color gamut display.
[0131] It can be seen from the data results of Example 1 and Examples 7-8 that if the heat treatment temperature is too low, the optimal crystallization temperature is not reached, the quantum efficiency is significantly reduced, and the wet-heat stability is poor; if the heat treatment temperature is too high, the crystallization temperature is too high, the quantum dots grow too large, resulting in devitrification of the quantum dot glass, decreased quantum efficiency, and significantly reduced wet-heat stability.
[0132] From the data results of Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, and Example 4 and Comparative Example 4, it can be seen that if zirconium is not doped, there is no effect of disconnecting the network structure of the glass matrix and improving the density, resulting in the inability to effectively improve the quantum efficiency and wet-heat stability.
[0133] It can be seen from the data results of Example 1 and Comparative Examples 5-6 that if the doping amount of zirconium dioxide is too little, the conditions for breaking the glass network structure and improving the density cannot be met, resulting in no significant improvement in quantum efficiency and wet-heat stability; if the doping amount of zirconium dioxide is too much, the glass network structure will be destroyed, the crystallization of quantum dots cannot be effectively controlled, and the glass matrix is too dense, resulting in a decrease in quantum efficiency, but the wet-heat stability is improved to a certain extent.
[0134] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A zirconium-doped all-inorganic perovskite quantum dot glass, characterized in that: In terms of molar percentage, the composition of the zirconium-doped all-inorganic perovskite quantum dot glass includes: Glass matrix: 68-89%, zirconium-containing compound: 0.1-1%, all-inorganic perovskite quantum dot matrix: 11-28%.
2. The zirconium-doped all-inorganic perovskite quantum dot glass according to claim 1, characterized in that: In terms of mole percentage, the raw material composition of the glass matrix includes: SiO2: 25-35%, B2O3: 35-40%, ZnO: 5-8%, CaO: 3-6%.
3. The zirconium-doped all-inorganic perovskite quantum dot glass according to claim 1 or 2, characterized in that: In terms of molar percentage, the raw material composition of the all-inorganic perovskite quantum dot matrix includes: Cs2CO3: 2-5%, PbO: 2-5%, KX: 7-18%, X = at least one of Cl, Br and I; Preferably, in terms of mole percentage, the composition of KX comprises: KBr: 2-8%, KI: 5-10%.
4. The zirconium-doped all-inorganic perovskite quantum dot glass according to any one of claims 1 to 3, characterized in that: The zirconium-containing compound includes at least one of zirconium dioxide, zirconium silicate and calcium zirconate; Preferably, the content of the zirconium-containing compound is 0.3-0.7% by mole percentage.
5. A method for preparing zirconium-doped all-inorganic perovskite quantum dot glass according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing the raw materials of the matrix glass, and then melting the obtained mixture to obtain a molten product; (2) heat treating the molten product to obtain the zirconium-doped all-inorganic perovskite quantum dot glass.
6. The preparation method according to claim 5, characterized in that: The mixing process in step (1) is accompanied by grinding; Preferably, the melting treatment in step (1) is carried out in an air atmosphere; Preferably, the temperature of the melting treatment in step (1) is 1000-1200°C; Preferably, the holding time of the melting treatment in step (1) is 5-20 minutes.
7. The preparation method according to claim 5 or 6, characterized in that: Before the molten product is heat treated in step (2), the molten product is first transferred to a mold at room temperature.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The temperature of the heat treatment is 500-550°C; Preferably, the heat treatment time is 3-12 h, preferably 7-10 h.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method comprises the following steps: (1) SiO2, B2O3, ZnO, CaO, Cs2CO3, PbO, KX and zirconium dioxide are fully ground and mixed according to their respective mole percentages to obtain a mixed powder; (2) In an air atmosphere, the mixed powder is melt-treated at 1000-1200° C. for 5-20 min. After the melting treatment, the molten product is transferred to a mold at room temperature, and then heat-treated at 500-550° C. for 3-12 h. After cooling to room temperature, the zirconium-doped all-inorganic perovskite quantum dot glass is obtained.
10. Use of the zirconium-doped all-inorganic perovskite quantum dot glass according to any one of claims 1 to 4 in the preparation of luminescent materials.